2020
DOI: 10.3390/w12092317
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Water Level Fluctuation and Concomitant Change of Nutrients Shift Microeukaryotic Communities in a Shallow Lake

Abstract: Seasonal water level fluctuations (WLFs) impose dramatic influences on lake ecosystems. The influences of WLFs have been well studied for many lake biotas but the microeukaryotic community remains one of the least-explored features. This study employed high-throughput 18S rRNA gene sequencing to investigate the spatiotemporal patterns of microeukaryotic communities in the dry and wet seasons with concomitant change of nutrients in Poyang Lake, which experiences huge seasonal WLFs. The results showed that the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 92 publications
0
3
0
1
Order By: Relevance
“…Water temperature, a key seasonal factor, may directly regulate microeukaryotic community composition (Liu et al, 2013). Prior investigations indicated that elevated water temperatures could enhance the proliferation of microeukaryotic species (Liu et al, 2020), partially explaining the higher species richness in the autumn compared to spring (Figure 1A). Nitrite (NO 2 -N) emerged as the sole nutrient significantly co-varied with microeukaryotic community structure during both seasons, as revealed by RDA ordination (Figures 9A,B).…”
Section: Discussionmentioning
confidence: 96%
“…Water temperature, a key seasonal factor, may directly regulate microeukaryotic community composition (Liu et al, 2013). Prior investigations indicated that elevated water temperatures could enhance the proliferation of microeukaryotic species (Liu et al, 2020), partially explaining the higher species richness in the autumn compared to spring (Figure 1A). Nitrite (NO 2 -N) emerged as the sole nutrient significantly co-varied with microeukaryotic community structure during both seasons, as revealed by RDA ordination (Figures 9A,B).…”
Section: Discussionmentioning
confidence: 96%
“…Thus, another reason for the lower diversity of planktonic microeukaryotes is the decreased suspended particle content and particle‐associated microbial species in river water. In contrast, the increased diversity in the downstream section may be explained by the higher NO 3 − and DSi concentrations in water, which could increase species diversity of planktonic microeukaryotes (Chen, Ren, et al, 2019; Liu et al., 2020; Zhang, Huang, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Los macroinvertebrados tuvieron su mayor abundancia en la época de sequía, debido a que en la temporada húmeda las lluvias desestabilizan el sustrato y este es arrastrado por la corriente, mientras que en época seca el sustrato se estabiliza y hay una acumulación gradual de macroinvertebrados (Arimoro et al, 2021). A la vez, la reducción del nivel del agua en la fase de sequía provoca cambios en la concentración de nutrientes que favorecen a ciertas comunidades (Liu et al, 2020).…”
Section: Composición De La Comunidad De Macroinvertebradosunclassified